Decision support for conceptual performance-based design. - Krawinkler, Helmut (Earthquake engineering & structural dynamics.)
Performance assessment implies that the structural, non-structural, and content systems are given and that decision variables, DVs, (e.g. expected annual loss, mean annual frequency of collapse) are computed and compared to specified performance targets. Performance-based design (PBD) is different by virtue of the fact that the building and its components and systems first have to be created. Good designs are based on concepts that incorporate performance targets up front in the conceptual design process, so that subsequent performance assessment becomes more of a verification process of an efficient design rather than a design improvement process that may require radical changes of the initial design concept. In short, the design approach could consist of (a) specifying performance targets (e.g. tolerable probability of collapse, acceptable dollar losses) and associated seismic hazards, and (b) deriving engineering parameters for system selection, or perhaps better, using the relatively simple design decision support tools discussed in this paper.